PET Imaging of Hepatocellular Carcinomas: F-Fluoropropionic Acid as a Complementary Radiotracer for F-Fluorodeoxyglucose - Jing Zhao MMed; Zhanwen Zhang MD; Dahong Nie MD; Hui Ma MD; Gongjun Yuan MD; Shu Su MMed; Shaoyu Liu DSc; Sheng Liu MD; Ganghua Tang DSc (Molecular Imaging)
Objective: To evaluate the preclinical value of 18 F-fluoropropionic acid ( 18 F-FPA) and 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) for imaging HCCs. Methods: The 18 F-FPA and 18 F-FDG uptake patterns in 3 HCC cell lines (Hep3B, HepG2, and SK-Hep1) were assessed in vitro and in vivo. The 18 F-FPA uptake mechanism was investigated using inhibition experiments with orlistat and 5-tetradecyloxy-2-furoic acid. The 18 F-FPA PET imaging was performed in different tumor animal models and compared with 18 F-FDG. We also evaluated the expressions of glucose transporter-1 (GLUT1), fatty acid synthase (FASN), and matrix metalloproteinase-2 (MMP2) in these cell lines. Results: In vitro experiments showed that the radiotracer uptake patterns were complementary in the HCC cell lines. Orlistat and 5-tetradecyloxy-2-furoic acid decreased the uptake of 18 F-FPA. The tumor-to-liver ratio of 18 F-FPA was superior to that of 18 F-FDG in the SK-Hep1 and HepG2 tumors ( P < .05). However, in the Hep3B tumors, the tumor-to-liver normalized uptake of 18 F-FDG was higher than 18 F-FPA ( P < .01). FASN was highly expressed in cell lines with high 18 F-FPA uptake, whereas GLUT1 was highly expressed in cell lines with high 18 F-FDG uptake. The 18 F-FPA uptake correlated with FASN ( r = 0.89, P = .014) and MMP2 ( r = 0.77, P = .002) expressions. Conclusions: PET imaging with 18 F-FPA combined with 18 F-FDG can be an alternative for detecting HCC.